Does employee readiness to change impact organization change implementation? Empirical evidence from emerging economy. Issue 2 (26th November 2021) - Rahi, Samar; Alghizzawi, Mahmoud; Ahmad, Sajjad; Munawar Khan, Mubbsher; Ngah, Abdul Hafaz
Abstract : Purpose: This study aims to gain insight into factors that impact employee readiness to change and organizational change management. Therefore, an integrative research model is developed with the combination of perceived competence, perceived relatedness, perceived autonomy, codification strategy and personalization strategy to investigate employee readiness to change. The research model tests the mediating role of employee readiness to change between factors underpinned self-determination theory, knowledge management strategy and organizational change management. In addition to the moderating role of self-efficacy is examined between the relationship of employee readiness to change and organizational change implementation. Design/methodology/approach: This research is conducted under a positive paradigm, and therefore, a quantitative research approach is incorporated to design a research strategy. The research model is empirically tested with a sample size of 361 employees working in commercial banks of Pakistan. For data analysis, the structural equation modelling approach is applied. Findings: Empirical findings indicate that altogether perceived competence, perceived autonomy, perceived relatedness, codification and personalization strategies had explained 76.8% variance in employee readiness to change. The effect size analysis shows that codification strategy has the largest impact in determining employee readiness to change. Therefore, the relatedness of employee tasks stands at the second stage in determining employee readiness to change. The predictive relevance of the research model is computed through blindfolding procedure and revealed substantial predictive relevance in measuring employee readiness to change. The findings of the research confirmed that the relationship between employee readiness to change and organizational change implementation will be stronger when self-efficacy is higher. Practical implications: The current research has several contributions to theory and practice. Theoretically, this research extends the self-determination theory with knowledge management strategy and enriches literature in employee readiness to change and organizational change management context. Practically, this research suggests that policymakers should focus on factors underpinned by self-determination theory and knowledge management model to develop a positive attitude among employees towards readiness to change. Similarly, self-efficacy is another important factor that moderates the relationship between readiness to change and change implementation and should be considered for managerial implication. Originality/value: This research is significant as it integrates two unique models, namely, the self-determination framework and the knowledge management model to investigate employee readiness to change. In addition to that, the research model is extended with the moderating effect of self-efficacy between the relationship of employee readiness to change and organizational change implementation.